Responsibility and joint production - Thomas Petersen; Malte Faber (University of Heidelberg, Department of Economics, 2004)
In this paper, we discuss the relationship between responsibility and joint production. Responsibility mirrors our ability to act freely. We can act freely only if we can assume responsibility for our actions and their consequences; the limits of our responsibility are therefore also the limits of our liberty (part I). Thus, a problem of responsibility arises from our partial ignorance with respect to the consequences which our actions entail. Since this ignorance is at least partly irreducible, we are often not able to control our actions sufficiently. As will become clear, this does not only hold for the social world. Correspondingly, a problem of responsibility emerges in nature and the environment from the phenomenon of joint production (part II). The implications hereof with regard to different forms of responsibility will be discussed in part III of the paper. Part IV draws conclusions and offers a perspective for the future.
Keywords: B4; H8; L5; O0; Q0; 330; Responsibility; ethics; environment; joint production; knowledge; ignorance; homo politicus; Wissen; Kuppelproduktion; Umweltbelastung; Verantwortung